Hard Skill dan Soft Skill Siswa dalam Ekstrakurikuler Hizbul Wathan : (Studi Kasus di SMK Muhammadiyah Semin) - Amirudin Yusuf; Mega Hidayati; Halim Purnomo (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2021)
This research is aimed at (1) identifying the types of hard skills and soft skills incorporated in Hizbul Wathan extracurricular at SMK (Vocational School) Muhammadiyah Semin (2) identifying the reinforcement of hard skills and soft skills within Hizbul Wathan extracurricular (3) identifying the impact of Hizbul Wathan extracurricular on students’ hard skills and soft skills. The type of this research was mixed-method research. The subjects of this research were teachers and students of class X. Data were collected through the methods of observation, interview, documentation, and questionnaire. The data were then analyzed through the methodology of data reduction, data display, conclusion, and verification. The research result shows that: (1) the hard skills output from the Hizbul Wathan extracurricular are products, handicrafts, and students’ score. Whereas, the soft skills are shown from students’ honesty, responsibility, just conduct, collaboration, adaptation skill, independence, communication skill, problem-solving skill, making decisions, critical thinking, tolerance, respect toward their peers, motivation, confidence, creativity, and discipline. (2) The hard skills’ reinforcement is done through training, competition, daily life application. Whereas, the soft skills’ reinforcement is done through group work training and problem-solving. (3) The impacts of Hizbul Wathan extracurricular on students’ hard skills and soft skills are shown through students’ ability to create a product, building independence, triggering socialization senses, and building collaboration. The conclusion to this research is that the attributions of soft skills have been implemented within the Hizbul Wathan extracurricular. Besides, Hizbul Wathan gives positive impacts on honing students' talent and developing their hard skills and soft skills.